(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The reform of the preschool education system in our country is recognized as a great renewal of the young generation, the future of our children. The role and importance of the preschool education system in the life of our society, which is the most important link in the upbringing of our children, cannot be measured by anything. It is the focus on pre-school education that will lay a solid foundation for the country’s future development.